Illegal removal of minors abroad in connection with child trafficking - Ripszám, Dóra (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
Human trafficking can be seen as a modern version of slavery; it is estimated to be the second most lucrative branch of international organized crime. According to the International Labour Organization (ILO), the profit from forced labour reaches $ 32 billion a year. One of the most vulnerable groups targeted by human traffickers are children. In view of the fact that Hungary can also be regarded as a country of origin, destination and transit for trafficking in human beings, it is necessarily intertwined with the phenomenon of the illegal removal of minors abroad. Acts involving the illegal removal of minors abroad do not constitute an independent legal category, this is a special umbrella term for when a minor is attempted to cross the border of the state of origin or current residence by other means of other means in breach of its legislation.